Low Frequency Sound Treatment Promoting Physical and Emotional Relaxation – Qualitative Study - Dr. , Heidi Ahonen (International Journal of Psychosocial Rehabilitation, 2013)
Low frequency sound has many applications to medicine but the efficacy and effectiveness of low fre- quency sound treatment in health prevention remains unclear. The purpose of this study was to explore the per- spectives and potentials of physioacoustic chair’s low frequency sound treatment when applied to daily activit - ies among a sample of music students, faculty and/or staff, and to examine how participants view the benefits of the intervention for their well-being, health and health-related activities. The results show that the physioacous - tic low frequency treatment added to participants’ subjective well-being by increasing their physical and emo- tional relaxation level, decreasing pain and stress, and increasing emotional enrichment and concentration. The study served as a pilot, to confirm stakeholder interest and to inform the feasibility of a larger study.